23‐1: HDR Imaging by Generating Multi‐Exposures from a Single Image for HDR/LDR Displays. Issue 1 (2nd June 2017) - Park, Jae Sung; Kil, Tae Ho; Cho, Nam Ik
Abstract : This paper presents a high dynamic range (HDR) imaging method that generates and fuses multiple exposures from a single image. We approximately estimate illumination using an edge‐preserving smoothing filter and adjusts it to several levels for generating multiple illuminations that correspond to multiple exposures in HDR image acquisition techniques. The low dynamic range (LDR) images of multi‐exposures are blended for reconstructing an HDR or tone‐mapped‐like LDR image for HDR/LDR displays.